Pore Types and Dolomite Reservoir Genesis of the Fifth Member of the Ordovician Majiagou Formation in the Central and Eastern Ordos Basin - Shilei Chen; Rong Dai; Shunshe Luo (Applied Sciences)
The Ordovician dolomite in the Ordos Basin is an important natural gas reservoir. Exploring dolomite genesis and the factors influencing reservoir characteristics is essential for deep carbonate rock exploration. This study offers a comprehensive analysis of dolomite evolution using methods such as thin-section petrography, isotope analysis, and trace and rare earth elements. The analysis shows that: Based on petrographic observations of the Majiagou Formation in the study area, the dolomite in the study area can be divided into residual oolitic dolomite of synsedimentary or metasomatic origin, micritic dolomite of secondary metasomatism or recrystallization origin, powder crystal dolomite, and fine crystal dolomite. Reservoir pores mainly develop intergranular pores, mold pores, dissolved pores, and fractures. Combined with the characteristics of major elements, trace elements, carbon and oxygen isotopes, rare earth elements, and inclusions in the study area, it can be concluded that the fifth member dolomite of the Majiagou Formation is of shallow–medium burial origin. The diagenetic evolution sequence from the penecontemporaneous period to the middle–deep burial period in the study area is penecontemporaneous dolomite, anhydrite dissolution → seepage silt filling, freshwater dolomite, calcite, and gypsum filling, pressure solution compaction, calcite partial dissolution → gypsum filling, karst cave, buried hydrothermal dolomite, dolomite partial dissolution → calcite complete dissolution, pore dissolution expansion, and quartz pyrite filling. In the early stage of compaction and pressure solution, the primary pores are rapidly reduced, and in the later stage, sutures are generated to provide channels for reservoir fluid migration. The recrystallization reduces the porosity during the middle–deep burial period.